Holy Prophet’s (ﷺ) Social Behavior, Research and Applied Review - Dr. Iftikhar Alam,; Dr. Khalid Mahmood Arif,; Ms. Shazia,; Dr. Muhammad Naveed,; Dr. Nadeem Abass, (Al-Qanṭara, 2023)
All the Prophets of Allah (Peace and blessing of Allah be upon them) established a righteous community based on the consciousness of resistance against the tyrannical rulers of their time and the tyrannical system established by them, trained and organized this community. Through this conscious, organized, trained collective, public opinion was smooth, the system of oppression was abolished and a system of justice and social equity was established. The Holy Prophet (peace be upon him) exercised an exemplary interaction with the depressed units of the society. Allah Almighty sent him as the blessing for all communities of society. The last Prophet Muhammad (peace be upon him) also followed the Sunnah of his predecessor Prophets) Peace and blessing of Allah be upon them) and established a conscious and welfare community to end the cruel system of the time and through this trained and organized group he ended the system of oppression and established the system of justice. In this paper, we’ll present the best example set by the Prophet Muhammad (Peace be upon him) regarding the social interaction and extract guidance from these examples for the sake of the modern society.